Grizzly and BlackBear: Structural Component Aging Simulation Codes. (3rd July 2021) - Spencer, Benjamin W.; Hoffman, William M.; Biswas, Sudipta; Jiang, Wen; Giorla, Alain; Backman, Marie A.
Abstract: The operating environment of nuclear reactors imposes extreme challenges on the materials from which the structures within and surrounding the reactor are constructed. Understanding the effects of exposure to this environment is critical for ensuring the safe long-term operation of these reactors. The Grizzly and BlackBear codes are being developed to model the progression of aging mechanisms and their effects on the integrity of critical structures. These codes take advantage of the capabilities of the MOOSE framework to solve the wide range of coupled physics problems that are encountered in predictive simulation of structural degradation. This paper provides an overview of these codes, with a specific focus on two capabilities relevant for light water reactor applications: reactor pressure vessel embrittlement and concrete degradation.